IEEE Std 802.3-2008/Cor 1-2009 (Corrigendum to IEEE Std 802.3-2008). IEEE Standard for Information technology-- Local and metropolitan area networks-- Specific requirements (IEEE, 2010)
The correction to the PAUSE reaction timing delay for the 10GBASE-T port type is addressed in this corrigendum to IEEE Std 802.3-2008.
Keywords: Collision detection (Computer animation); Information technology.; Local area networks (Computer networks)